Legal Culture of the State Law Enforcement Service in the Republic of Belarus: Activity and Value-Normative Aspects - I. A. Demidova (Сибирское юридическое обозрение, 2020)
The importance of law enforcement in all spheres of public life, as well as public administration is conditioned by the objective need to ensure law and order in society. The creation of an effective law enforcement system in Belarus is a priority area for the improvement of law enforcement in modern society. Increasing the professionalism of State law enforcement officials is designed to foster a legal culture and a positive attitude of society towards the subjects of law enforcement activities. In the context of the study of the legal culture of modern Belarusian society the actual doctrinal and practical task is to characterize the activity and value-normative basis of the state law enforcement service. The article presents the analysis of theoretical approaches and legislative practice to the designation of qualifying features of state law enforcement agencies, the allocation of their system. Law enforcement service is distinguished from other types of state service in accordance with functional and organizational criteria.